Ground-state properties of the retinal molecule: from quantum mechanical to classical mechanical computations of retinal proteins - Bondar, Ana-Nicoleta; Knapp-Mohammady, Michaela; Suhai, Sándor; Fischer, Stefan; Smith, Jeremy C. (Theoretical chemistry accounts, 2011)
Retinal proteins are excellent systems for understanding essential physiological processes such as signal transduction and ion pumping. Although the conjugated polyene system of the retinal chromophore is best described with quantum mechanics, simulations of the long-timescale dynamics of a retinal protein in its physiological, flexible, lipid-membrane environment can only be performed at the classical mechanical level. Torsional energy barriers are a critical ingredient of the classical force-field parameters. Here we review briefly current retinal force fields and discuss new quantum mechanical computations to assess how the retinal Schiff base model and the approach used to derive the force-field parameters may influence the torsional potentials.